Study of the Total Ownership Cost of Electric Vehicles in Romania - Lucian-Ioan Dulău (World Electric Vehicle Journal)
Due to the significant increase in the number of EVs, this manuscript presents a study of the total ownership cost of electric vehicles in Romania. The total cost of ownership (TCO) includes the initial purchase price, maintenance costs, power prices, and government incentives or subsidies unique to the market in Romania. The TCO was calculated for battery electric vehicles (BEVs) and internal combustion vehicles (ICEs). Several vehicles were selected for the study, representing the models with the highest sales in Romania and a similar price range. The results show that EVs have a lower TCO compared with internal combustion vehicles if the battery replacement cost for EVs is not considered in the analysis. If this cost is considered, the TCO for the BEVs has a significant increase due to the high cost of the battery. Another analysis performed regards the CO2 emissions. These are higher for ICEs compared to BEVs, so the BEVs help reduce emissions.